Effect of Extracellular Crude Protein (ECP) on expression IL-1, IL-6, IFN- in nile tilapia (Oreochromis niloticus) - Cucun Herlina; Mohammad Fadjar; Maftuch Maftuch; Uun Yanuhar (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Modern strategies incorporate preventive measures such as extracellular products, as soluble proteins with antigenic properties, as well as generating a broad immune response. The aim of research is to determine and analyze the effect of the extracellular product of E. tarda on enhancing the immunity of Nile tilapia (O. niloticus). The research design with treatment durations of d0, 3rd, 6th, 9th day, and control (A, B, C, D, K). ECP vaccination was injected intraperitoneally at a dose of 0.1 ml/fish. The parameters analyzed are the expression of IL-1, IL-6, and IFN-, phagocytic activity, leukocyte differential, total white blood cells, and relative percent survival. The results of phagocytosis activity were highest in treatment C at 84.18% 1.81. The highest leukocyte differential in treatment C was lymphocytes at 56% 2.00, monocytes at 28% 2.00, and 16% 0.00, with a total leukocyte count of 29 x 10^3 cells 2.64, and RPS values ranging from 83.33% to 100% over 9 days of post-vaccination maintenance. Then, post-vaccination, there was an increase in the expression levels of the cytokine genes IL-1 and IL-6, but there was no increase in the expression levels of the IFN- gene compared to the control in Nile tilapia. (O. niloticus).Keywords:ECPIL-1IL-6IFN-Immune Response